Comparison of Provenance of the Injana and Mukdadiya Formations in Zorbatiya area, Wasit Governorate, East of Iraq - Al-dabbagh, Neaam Omar; Tamar-Agha, Mazin Y. (Iraqi Journal of Science, 2018)
Petrographic, heavy mineral and clay mineral analyses are carried out for the sandstone and the mudstone units of Injana and Mukdadiya Formations in Zorbatiya area, Wasit Governorate, East of Iraq. The sandstones and the mudstones are nested as repeated fining–upwards successions, representing fluvial deposits. The sandstones of the Mukdadiya Formation is gravelly and on occasions becomes conglomerate. The sandstone of both formations comprises rock fragments, quartz and feldspars. The rock fragments are the dominant component consisting sedimentary, igneous and metamorphic rock fragments, accordingly these sandstone are classified as litharenite. The clay minerals of the mudstone units are mostly illite, kaolinite, chlorite and mixed-layered clay. The mineralogic and petrographic data suggest the derivation of Injana and Mukdadiya Formations from nearby sources with contribution from igneous, metamorphic and sedimentary provenance and deposited in arid climate. The Mukdadiya deposits are rich with Paleogene deposits, some of which are coarse and cobbly.